Health support network used by mothers of children/adolescents with cerebral palsy - Freitag, Vera Lucia; Milbrath, Viviane Marten; Petroni, Sidnei; Cosentino, Susane Flôres; Cabral, Fernanda Beheregaray; Colomé, Isabel Cristina dos Santos (Journal of Health Care, 2017)
Introduction: The mother/caregiver of child/adolescent with cerebral palsy lives an overload on a daily basis. In this sense, there is need for a health support network so they can take care of the child, not dismissing the care of themselves. Objective: To know the health support network used by caregivers/mothers of children/adolescents with cerebral palsy for the care of themselves. Methodology: Exploratory and descriptive study with a qualitative approach, carried out from May to July 2015 in a city north of Rio Grande do Sul, Brazil. The study included ten mothers/caregivers. Data collection occurred from the semi-structured interviews and were examined according to the thematic analysis of Minayo. Results: The results showed that the health support network of these mothers consists of the institutional and the Basic Health Unit dimensions, focused mainly on the figure of the Community Health Agent. Conclusions: Expansion and consolidation of a multidisciplinary network support are recommended in order to facilitate access to health care and quality of life to these mothers/caregivers.
Keywords: Caregivers; Primary Care Nursing; Public Health; Mothers; Cerebral Palsy